Conversion of oxidative combustion into powerful thermal and light energy - Khasanov, Kholmurad (Edelweiss Applied Science and Technology, 2024)
The phenomenon of transformation of the oxidative combustion of natural coolants - coal, methane, propane, etc. - into the production of powerful light and thermal energy when their combustion zone is exposed to supersonic spiral-twisted jets of dusty plasma from a dynamic emitter has been experimentally discovered. The phenomenon occurs without emissions of harmful substances from chemical combustion that contribute to the greenhouse effect. The structure of dusty plasma jet is a self-compressing double helix with collective resonant oscillations. The phenomenon opens up a new type of energy production, connected with a conversion of coal into aluminosilicate minerals, etc.